Gonadal microplastic-like particle occurrence and gamete quality of Cyprinus carpio along the Brantas River Basin gradient, East Java, Indonesia - GRETANIA RESIDIWATI; GALUH CHANDRA AGUSTINA; VISKI FITRI HENDRAWAN; DJOKO HARTONO; MUHAMAD ARFAN LESMANA; SHEHU SIDI; DYAH KINASIH WURAGIL PUTU RAHARJO; AULANNI’AM AULANNI’AM; BUDIONO BUDIONO; UMAR BELLO; ILHAM ARTA WIGUNA; AHDA SABILA; HABIB SYAIFUL ARIF TUSKA (Society for Indonesian Biodiversity, 2026)
Abstract. Residiwati G, Sabila A, Wiguna IA, Bello U, Budiono, Aulanni’am A, Raharjo DKWP, Sidi S, Lesmana MA, Hartono D, Hendrawan VF, Agustina GC, Tuska HSA. 2026. Gonadal microplastic-like particle occurrence and gamete quality of Cyprinus carpio along the Brantas River Basin gradient, East Java, Indonesia. Biodiversitas 27 (5): d270529. https://doi.org/10.13057/biodiv/d270529. Microplastic contamination is an emerging concern in freshwater ecosystems because of its potential to impair fish reproductive performance. This field-based comparative study evaluated site-level patterns of environmental particle occurrence, gonadal occurrence of microplastic-like particles, and gamete quality in Cyprinus carpio collected from four locations along the Brantas River Basin, East Java, Indonesia, during May-July 2025. A total of 32 males and 32 females were examined, with 8 males and 8 females obtained from each site through four sampling replicates, in which two fish of each sex were collected per replicate. Water particle occurrence was derived from one processed sample per site and was therefore interpreted descriptively, whereas gonadal tissues were examined for morphologically identified microplastic-like particles. Reproductive quality was assessed through sperm motility, viability, morphological abnormalities, and DNA integrity, as well as oocyte diameter, survival rate, and germinal vesicle breakdown (GVBD). Microplastic-like particles were detected at all sites in both water and gonadal tissues, with higher occurrence at downstream locations than at the uppermost site. This pattern was accompanied by poorer reproductive parameters. In males, downstream fish showed lower sperm motility and viability together with higher morphological abnormalities and greater DNA damage. In females, downstream fish exhibited smaller oocyte diameter, lower survival rate, and reduced GVBD. One-way ANOVA indicated significant differences among sampling sites for all reproductive endpoints (p<0.001). Overall, higher site-level particle occurrence co-occurred with poorer gamete quality under field conditions. These results provide comparative field-based evidence that reproductive condition in C. carpio varied systematically along a site gradient in the Brantas River Basin.